2005
DOI: 10.1038/sj.emboj.7600900
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB p50 promotes HIV latency through HDAC recruitment and repression of transcriptional initiation

Abstract: Cells latently infected with HIV represent a currently insurmountable barrier to viral eradication in infected patients. Using the J‐Lat human T‐cell model of HIV latency, we have investigated the role of host factor binding to the κB enhancer elements of the HIV long terminal repeat (LTR) in the maintenance of viral latency. We show that NF‐κB p50–HDAC1 complexes constitutively bind the latent HIV LTR and induce histone deacetylation and repressive changes in chromatin structure of the HIV LTR, changes that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
441
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(467 citation statements)
references
References 31 publications
(35 reference statements)
22
441
0
4
Order By: Relevance
“…5C and D), and the use of TSA, which induces expression through a different mechanism than TNF (32), corroborates this observation (SI Appendix). This observed decrease in k off with TNF induction leads to extended duration of bursts and is consistent with the reported inhibition of p50-HDAC1 repressivecomplex formation at LTR NFκB sites by p50/RelA heterodimers (33)-the successful formation of HDAC1 leads to weakened recruitment of RNA polymerase II and weakened transcriptional initiation (34). The observed increases in k on are also consistent with increased recruitment of RNA polymerase II to the LTR promoter NFκB sites induced by TNF (35,36).…”
Section: Resultssupporting
confidence: 87%
“…5C and D), and the use of TSA, which induces expression through a different mechanism than TNF (32), corroborates this observation (SI Appendix). This observed decrease in k off with TNF induction leads to extended duration of bursts and is consistent with the reported inhibition of p50-HDAC1 repressivecomplex formation at LTR NFκB sites by p50/RelA heterodimers (33)-the successful formation of HDAC1 leads to weakened recruitment of RNA polymerase II and weakened transcriptional initiation (34). The observed increases in k on are also consistent with increased recruitment of RNA polymerase II to the LTR promoter NFκB sites induced by TNF (35,36).…”
Section: Resultssupporting
confidence: 87%
“…Similar amounts of NF-B p50 subunit were detected both before and after TNF-␣ stimulation, which we think is consistent with previous observations that low levels of the p50 subunit are present on specific NF-B-responsive promoters in the nucleus of unstimulated cells as the p50 homodimer, whereas the majority of this subunit is retained in the cytoplasm as RelA/p50 (33)(34)(35). The p50 homodimer itself does not contain transactivation domains, but it associates with promoter regions of some NF-B-dependent genes, including integrated HIV-1 LTR in the unstimulated conditions (36). However, Brm, BRG1, and DPF3 were all detected at the promoter even before stimulation, and their recruitment levels were not significantly changed upon exposure to TNF-␣, apart from Brm, which showed elevated levels at the promoter (right panel of Fig.…”
Section: Kinetics Of Rela Recruitment Upon Tnf-␣ Stimulation Correlatsupporting
confidence: 93%
“…This change occurred within 24 h and was sustained for 11 days. This is particularly significant because previous studies have demonstrated that elevated levels of HDAC1 are associated with the 5Ј-LTR of latent forms of HIV-1 and repressive changes in chromatin structure of the HIV-1 promoter region (41)(42)(43)(44)(45)(46)(47)(48). In contrast, prom-D induced a less marked recruitment of HDAC1 at day 1.…”
Section: Resultsmentioning
confidence: 99%